Addition of Plastic Mixture (LDPE) for the Development of Alternative Mixtures in Concrete Blocks - Abdullah, Abdullah; Erna Yuliwati; Eka Sri Yusmartini (Asosiasi Riset Teknik Elektro dan Infomatika Indonesia, 2025)
This study investigates the potential of Low-Density Polyethylene (LDPE) plastic waste as a partial substitute for sand in concrete block mixtures, focusing on its effects on compressive strength and water absorption. LDPE is a non-biodegradable plastic waste that poses significant environmental challenges. Its incorporation into construction materials offers a promising solution to reduce pollution while enhancing the performance of building components. The research employed LDPE substitution levels of 10%, 15%, 20%, 25%, and 30% by weight of sand, compared against conventional concrete blocks without LDPE. Experimental results revealed that the highest compressive strength was achieved with a 15% LDPE mixture, reaching 80.762 kg/cm² at 28 days of curing—an increase of approximately 40.8% compared to normal blocks, which recorded 57.359 kg/cm². LDPE additions up to 20% maintained favorable strength characteristics, while higher proportions (25% and 30%) led to a decline in mechanical performance. In terms of water absorption, the inclusion of LDPE demonstrated a decreasing trend, attributed to the hydrophobic nature of plastic, which enhances moisture resistance in the concrete blocks. These findings suggest that a 15% LDPE substitution represents an optimal formulation for producing eco-friendly concrete blocks with improved strength and reduced water absorption. The study highlights the dual benefits of waste management and material innovation, aligning with sustainable development goals. By repurposing plastic waste into construction applications, this approach not only mitigates environmental impact but also contributes to the advancement of green building technologies. Further research is recommended to explore long-term durability, thermal properties, and scalability of LDPE-based concrete products in real-world construction settings.